Pedagogik Inovatif: Upaya Meningkatkan Motivasi Belajar dan Kemampuan Literasi Anak di Pulau Mapur Bintan - Wijayanto, Fery; Hidayatunnajah, Ai; Lestari, Amilia; Susilawati, Etic; Kamaludin, Mohamad Imam (Jurnal Dharma Bhakti Ekuitas, 2024)
This article aims to review community service activities on Mapur Island, Bintan Pesisir, and Riau Islands. This service activity is based on the premise that social problems exist, such as low levels of children's learning motivation, development of potential interests and talents, and children's literacy skills. The purpose of this article is to analyze each stage or cycle of service and its benefits to improve the quality of education on Mapur Island. The Participatory Action Research (PAR) method is used in service activities carried out through the stages or cycles of the action research method, namely, social reflection, social mapping, participatory planning, and action implementation. The results showed that the innovative pedagogy program on Mapur Island, through inspirational classes can foster children's learning motivation, peer counseling can identify children's potential talent interests, and reading corners can improve children's literacy skills. The benefits include improved academic skills, learning motivation, and understanding of the importance of education. In addition, the program creates an environment that supports the development of children's academic potential and community awareness of the importance of education for children's future. It can be concluded that community service activities on Mapur Island, Bintan Pesisir, and Riau Islands have successfully contributed to improving children's reading, writing, and counting literacy skills, as well as children's learning motivation through inspirational classes and recommending the potential of children's talent interests through peer counseling programs. Keywords: Pedagogic, Innovative, Motivation, Literacy, Service Abstrak Pengabdian ini bertujuan untuk mengkaji tentang kegiatan pengabdian masyarakat di Pulau Mapur, Bintan Pesisir, Kepulauan Riau. Kegiatan pengabdian ini dilaksanakan atas dasar permasalahan sosial seperti: motivasi belajar anak, pengembangan potensi minat bakat dan kemampuan literasi anak masih terbilang rendah. Tujuan pengabdian ini untuk menganalisis setiap tahapan atau siklus pengabdian dan manfaatnya untuk meningkatkan kualitas pendidikan di Pulau Mapur. Metode Participatory Action Research (PAR) digunakan dalam kegiatan pengabdian yang dilaksanakan melalui tahapan atau siklus metode riset aksi yakni, refleksi sosial, pemetaan sosial, perencanaan partisipatif dan pelaksanaan aksi. Hasil penelitian menunjukan program pedagogi inovatif di Pulau Mapur, melalui kelas inspiratif dapat menumbuhkan motivasi belajar anak, peer counseling dapat mengidentifikasi potensi minat bakat anak, dan pojok bacaan dapat meningkatkan kemampuan literasi anak. Manfaatnya meliputi peningkatan kemampuan akademis, motivasi belajar, dan pemahaman akan pentingnya pendidikan. Selain itu, program ini dapat menciptakan lingkungan yang mendukung pengembangan potensi akademik anak dan kesadaran masyarakat akan pentingnya pendidikan bagi masa depan anak-anak. Dapat disimpulkan bahwa kegiatan pengabdian masyarakat di Pulau Mapur, Bintan Pesisir, Kepulauan Riau berhasil memberikan berkontribusi terhadap peningkatkan kemampuan literasi membaca, menulis dan menghitung anak, sekaligus motivasi belajar anak melalui kelas inspiratif dan merekomendasikan potensi minat bakat anak melalui program peer counseling. Kata kunci: Pedagogik, Inovatif, Motivasi, Literasi, Pengabdian